Balanced ratio of plasma to packed red blood cells improves outcomes in massive transfusion: A large multicenter study - YANG, JIANG-CUN (Exp Ther Med, 2015)
Resuscitation with the early administration of plasma can improve the survival of patients undergoing surgery or trauma patients who require massive transfusion. To ascertain the optimal ratio of fresh frozen plasma (FFP) to packed red blood cells (pRBCs) in massive transfusions, the records of 1,048 patients who received a massive transfusion at 20 hospitals were retrospectively reviewed. The patients were stratified into three groups according to the ratio of FFP to pRBCs. These were the low (<1:2.3), middle (1:2.3–0.75) and high (≥1:0.75) ratio groups. For 24-h treatment, the middle FFP:pRBC ratio led to a lower mortality rate (9.31%) compared with that in the low (11.83%) and high (11.44%) ratio groups (P=0.477). For 72-h treatment, the middle FFP:pRBC ratio also lead to the lowest mortality rate (7.25%), which was significantly lower than the ratios in the low (10.39%) and high (13.65%) ratio groups (P=0.007). The length of hospital stay, ICU stay, and FFP:pRBC ratio in 72 h were found to be significant associated with mortality. The optimal ratio of FFP to pRBCs of 1:2.3–0.75 in 72 h can improve the survival of patients undergoing massive transfusions.